Community, kinship and piety: Lincoln Cathedral close c.1450-1500 - Wilson, Marianne Louise (2014)
This thesis provides an analysis of the unique nature of the community living in Lincoln Cathedral close in the late fifteenth century. The medieval cathedral close is an important unit of study which has been overlooked in existing historiography. This research draws attention to a hitherto neglected area. Testamentary evidence from inhabitants of the close is used, in conjunction with other sources, to analyse the individuals who constituted the close community, particularly their priorities and concerns prior to death. The first chapter outlines the structure of the cathedral hierarchy and analyses archaeological and architectural evidence for the nature of housing available to close inhabitants. The second chapter examines the identities of the close inhabitants and uses evidence of personal wealth extracted from testamentary bequests to delineate social status. The geographical origins and connections of a number of the close inhabitants are evaluated by identifying the locations to which testamentary bequests were made. Evidence for the education, careers and cultural interests of the close inhabitants are also explored. The third chapter surveys relationships within and without the close. It investigates case studies of testamentary legacies made to fellow close inhabitants, friends and family, as well as the executors chosen. The final chapter considers evidence for the different testamentary strategies employed in the pious, commemorative and charitable provision of the clergy, laywomen and laymen living in the close. It also explores the nature of local and communal pieties expressed by the community. The outcome of this study is to shed light on the character of the community inhabiting Lincoln Cathedral close c.1450-1500, which consisted of a high proportion of laypeople and clergy, mainly local to the city and diocese and largely from the lower ranks of society. As this study emphasises, a small proportion of higher clergy attended university and valued this education, with book ownership indicating in particular the scholarly interests of the close inhabitants. In addition to this, the specific housing arrangements meant that there was a high level of integration between the close inhabitants, whilst reinforcing social hierarchy there. Strong relationships also developed between the chapter clergy, whilst family relationships and friendships were more important for the laity. Lincoln Cathedral was a central concern of the close inhabitants' pious devotions, with different groups of testators adopting different approaches to commemoration and charity, reflecting their distinct roles within medieval urban society.